Influence of surface defects on the vortex penetration and arrangement at mesoscopic superconducting samples - Benites, T. N.S. [UNESP]; Presotto, A. [UNESP]; Barba-Ortega, J.; Sardella, E. [UNESP]; Zadorosny, R. [UNESP] (IOP Publishing, 2024)
All superconductor applications lie on carry dissipationless current; however, in the presence of external magnetic fields, including the self-field, vortices penetrate the sample, and their dissipative motion generates resistive states. Thus, once the superconducting state survives for higher magnetic fields due to the presence of vortices, those specimens cannot move to increase the material's critical current density; thus, in this work, we studied the influence of surface defects on the vortex penetration at square mesoscopic superconducting materials using the time-dependent Guinzburg-Landau framework. The lateral size of the samples was 12 times the coherence length at zero Kelvin, with defects distributed in two opposite borders. The main result showed that the currents crowd around the surface defects are responsible for vortex penetration at 60% of critical temperature.